Attenuation characteristics of monolayer graphene by Pi- and T-networks modeling of multilayer microstrip line. (September 2017) - Sharma, Pulkit; Singh, Sumit Pratap; Patel, Kamlesh
Abstract: The impedances of Pi- and T- networks are obtained from the measured S -parameters of the multilayer microstrip line by modeling as an attenuator. The changes in impedances have been analyzed for the properties of various superstrates at the microwave ranges. With graphene on glass and graphene on quartz loadings, the impedances have increased and shifted towards lower frequency more in Pi-network than T-network modeling. This shift has become more prominent at higher frequency for the graphene on glass than graphene on quartz. A little increase in attenuation is found for graphene on glass or quartz than bare glass and quartz. The present study can be extended to obtain attenuation characteristic of any thin film by simple experimental method in the microwave frequencies.